Ways to Success in Education: Students’ Behavioral Strategies in Regional Universities of Russia - P. A. Ambarova; G. E. Zborovsky (Высшее образование в России)
The article discusses the behavioral strategies of students of regional Russian universities, focused on achieving educational success. The situation of uncertainty in modern higher education is shown as a social context that determines the variability of students’ behavioral strategies. A factor that has a significant impact on the phenomenon under study is the change in the views of the main educational communities (teachers and students) about educational success: the expansion of the range of its components, differentiation among different groups of students, orientation to non-educational benefits and values that can be obtained by university graduates in the future at the expense of educational capital. Based on the data of an empirical study conducted in the universities of the Sverdlovsk region in 2019-2021, the characteristic of behavioral strategies for achieving educational success implemented by students of Ural universities is given. It is noted that strategies for achieving success in education begin to be formed in the pre-university period, as part of the transition from school to university. It is concluded that during the university period, in response to new goals and learning difficulties, different groups of students develop four types of behavioral strategies – traditional, innovative, imitation, and «withdrawal» strategies.